The Agriculture-Forest Interface Is the Key to Achieving Global Restoration Goals - De Pinto, Alessandro (2017)
Senior Research Fellow Alex De Pinto's presentation at IUCN side event at COP23 (November 2017) Land and forest degradation is a global problem and must be addressed globally.